Implementasi Etika Bisnis Islam Dalam Produksi Usaha Jamur Tiram Di Desa Sokogrenjeng Kecamatan Kenduruan Kabupaten Tuban - Nurul Azizah, Siti; Agus Sifa', Moh.; Kuncoro Putro, Heri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to analyze the implementation of Islamic business ethics in the production of oyster mushrooms in Sokogrenjeng Village, Kenduruan District, Tuban Regency. The research method used is a qualitative descriptive research method, namely by describing or describing the conditions that occur in the field. Data collection techniques were carried out using interviews, observation and documentation. The research results obtained by researchers show that oyster mushroom business owners have applied the principles of Islamic business ethics starting from unity/tawhid, justice, free will, responsibility, and truth/honesty. This can be seen from various aspects of the business implemented starting from the selection of raw materials and the production process. This research shows that the implementation of Islamic business ethics in the oyster mushroom business in Sokogrenjeng Village is highly recommended because it has a positive impact on business owners, consumers and the environment. Apart from that, it can increase consumer confidence, improve business image, and create a just and prosperous society. Business owners get blessings in this world and the hereafter. It is hoped that this research can contribute to improving the implementation of Islamic business ethics in the oyster mushroom business in Sokogrenjeng Village, so that it can produce halal, quality products that are beneficial to the community.